Why Russia is reviving its conventional military power - Renz, Bettina (US Army War College, 2016)
The revival of Russian military power poses certain challenges to NATO and to the West. However, the exact nature of these challenges is not straightforward. This article discusses why Russia is reviving its conventional military power and argues these developments are not limited to the intention of preparing for offensive action. NATO’s and the West’s policy responses to recent changes in Russian defense policy need to be based on a realistic and nuanced understanding of Russian motivations because ill-considered responses could have serious unintended consequences.